2021
DOI: 10.3390/microorganisms9071539
|View full text |Cite
|
Sign up to set email alerts
|

Application and Perspectives of MALDI–TOF Mass Spectrometry in Clinical Microbiology Laboratories

Abstract: Early diagnosis of severe infections requires of a rapid and reliable diagnosis to initiate appropriate treatment, while avoiding unnecessary antimicrobial use and reducing associated morbidities and healthcare costs. It is a fact that conventional methods usually require more than 24–48 h to culture and profile bacterial species. Mass spectrometry (MS) is an analytical technique that has emerged as a powerful tool in clinical microbiology for identifying peptides and proteins, which makes it a promising tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 135 publications
(172 reference statements)
0
45
0
Order By: Relevance
“…Consequently, it is not possible to attribute with certainty those cases to lactobacilli also because a strictly related bacterium, Eggerthia catenaformis , considered to belong to the old genus Lactobacillus until 2011, is capable of causing infections [ 76 , 77 , 78 , 79 ] and can be confused with lactobacilli at the phenotypic level [ 80 ]. The studies that reported identification to the species level without reference to the identification method ( Table 1 ) probably used standardized colorimetric tests or MALDI-TOF mass spectrometry, largely applied in clinical laboratories [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is not possible to attribute with certainty those cases to lactobacilli also because a strictly related bacterium, Eggerthia catenaformis , considered to belong to the old genus Lactobacillus until 2011, is capable of causing infections [ 76 , 77 , 78 , 79 ] and can be confused with lactobacilli at the phenotypic level [ 80 ]. The studies that reported identification to the species level without reference to the identification method ( Table 1 ) probably used standardized colorimetric tests or MALDI-TOF mass spectrometry, largely applied in clinical laboratories [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of MALDI-TOF MS in microbiological diagnostics significantly shortens the time needed for pathogenic bacteria or fungal identification [ 42 , 43 , 44 , 45 ]. Nevertheless, much care is needed with sample preparation to overcome identification failures.…”
Section: Discussionmentioning
confidence: 99%
“…Before the TLA era, the development of matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) for the identification of bacteria, mycobacteria, yeasts, and molds has fundamentally replaced the well-established conventional diagnostic methods for identifying microorganisms, which were based essentially on biochemistry testing. In comparison with the conventional phenotype methods or molecular assays used in the identification of microorganisms, MALDI-TOF/MS has several advantages which can be summarized in three points: rapid turnaround time, low specimen volume requirements, and moderate reagent costs (Cherkaoui et al, 2010;Cherkaoui et al, 2011;Gaillot et al, 2011;Kaleta et al, 2011;Tan et al, 2012;Barberis et al, 2014;Verroken et al, 2016;Faron et al, 2017;Chen et al, 2021;Torres-Sangiao et al, 2021). Accurate and rapid identification of microorganisms using MALDI-TOF/MS helped to quickly support treatment decisions, especially when the infecting pathogen was unexpected.…”
Section: Improving Turn-around Times (Tat) In Clinical Bacteriologymentioning
confidence: 99%